The PASS to superior reading performance. (3rd July 2018) - Dunn, Kristy; Georgiou, George K.; Das, J. P.
ABSTRACT: Although the role of cognitive processes, such as planning, attention, simultaneous, and successive (PASS) processing in reading ability has been examined in samples of typically developing children and children with reading difficulties, it remains unclear if these processes also contribute to superior reading performance. Thus, in this study we examined (a) which PASS processes differentiate superior readers from average readers and (b) what is the individual profile of the superior readers. Thirty-six children with superior reading performance (standard score in Broad Reading equal to or higher than 130) and 43 average readers (standard score in Broad Reading between 85 and 115) were assessed on measures of general intelligence, planning, attention, simultaneous, and successive processing. The results of multivariate analyses indicated that the superior readers performed significantly better than the average readers only in simultaneous and successive processing. However, the superior readers exhibited diverse individual profiles of cognitive assets. The psychoeducational implications of these findings are discussed.